Government responsiveness on safety and security of Malaysia music festivals - Ismail, Khairiah; Abdullah, Nawal Hanim; Zamzuri, Norol Hamiza; Bali Mahomed, Anuar Shah (Global Academic Excellence (M) Sdn Bhd, 2022)
Music festivals are often viewed as events that attract a large number of attendees. Despite their positive economic, environmental, and policy impacts on host cities, there are always safety and security concerns at music festivals. This paper emphasises the significance of having proper safety and security, with a particular focus on Malaysian music festivals. The perspectives of government agencies were sought to acquire evidence regarding the impact of a safe and secure music festival, as the approval or rejection of music festivals is dependent on them. Previous studies have highlighted the importance of safety and security at music festivals. However, studies on the perspectives of government agencies, particularly in the context of Malaysian music festivals, are limitedly explored. Therefore, this study aims to investigate the importance of safety and security at music festivals and the repercussions of their absence. Qualitative approaches employed in this study included semi-structured interviews with government agencies such as municipal councils, police, Malaysian Volunteer Corps Department (RELA), and ministries, observation at Malaysian music festivals, and document analysis. The data were then analysed using thematic analysis. The findings of the current study provide evidence of the impact of effective security and safety on the success of music festivals.